(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The article is a Measuring Job Satisfaction in public and private school teachers. ‘Job satisfaction’ refers to the attitudes and feelings people have about their work. Positive and good attitudes towards the job show job satisfaction. Negative and adverse attitudes towards the job show job dissatisfaction. There has also been significant interest in the complicated relationship among an individual’s job satisfaction and satisfaction with other aspects of his or her life. It was put forwarded to study of job satisfaction in public and private school teachers. To test this hypothesis the researcher conducts this study to examine the teacher’s job satisfaction. A questionnaire was developed with 25 items and 5 options. A sample of 400 public and private school teachers was selected for the study.